2020
DOI: 10.1155/2020/6538930
|View full text |Cite
|
Sign up to set email alerts
|

Andrographolide Exerts Antihyperglycemic Effect through Strengthening Intestinal Barrier Function and Increasing Microbial Composition of Akkermansia muciniphila

Abstract: Accumulating evidence indicates that type 2 diabetes (T2D) is associated with intestinal barrier dysfunction and dysbiosis, implying the potential targets for T2D therapeutics. Andrographolide was reported to have several beneficial effects on diabetes and its associated complications. However, the protective role of andrographolide, as well as its underlying mechanism against T2D, remains elusive. Herein, we reported that andrographolide enhanced intestinal barrier integrity in LPS-induced Caco-2 cells as ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 48 publications
0
20
0
Order By: Relevance
“…Moreover, many other metabolites linked to ROS production and apoptosis (Chao et al, 2019) (3,5-DMA [3,5-Dimethylaniline]), and liver cirrhosis (pipecolinic acid, a metabolite of lysine) (Kawasaki et al, 1988), were reduced (Figure S6D), whereas the levels of medium-chain dicarboxylic acids (MCDAs) were increased in WPI relative to CAS (Figure S6D). Azelaic acid possesses anti-in-flammatory properties, suberic and sebacic acids are microbial metabolites formed from breakdown of oleic and linoleic FAs, and andrographolide is a known promoter of growth of A. muciniphila (Su et al, 2020), as seen in WPI-fed animals. Along with upregulation of microbial FA biosynthesis pathways, 30% WPI groups, with their potential to bind dietary fat, had increased fecal TAGs relative to CAS at 55% fat (Figure S6E).…”
Section: Hypothalamic Transcriptome Responded To High Wpi With High Fatmentioning
confidence: 99%
“…Moreover, many other metabolites linked to ROS production and apoptosis (Chao et al, 2019) (3,5-DMA [3,5-Dimethylaniline]), and liver cirrhosis (pipecolinic acid, a metabolite of lysine) (Kawasaki et al, 1988), were reduced (Figure S6D), whereas the levels of medium-chain dicarboxylic acids (MCDAs) were increased in WPI relative to CAS (Figure S6D). Azelaic acid possesses anti-in-flammatory properties, suberic and sebacic acids are microbial metabolites formed from breakdown of oleic and linoleic FAs, and andrographolide is a known promoter of growth of A. muciniphila (Su et al, 2020), as seen in WPI-fed animals. Along with upregulation of microbial FA biosynthesis pathways, 30% WPI groups, with their potential to bind dietary fat, had increased fecal TAGs relative to CAS at 55% fat (Figure S6E).…”
Section: Hypothalamic Transcriptome Responded To High Wpi With High Fatmentioning
confidence: 99%
“…At species level, Akkermansia muciniphila, has received attention because of its specific biological properties including immune modulation, wound healing, and SCFA production [32]. Moreover, various studies have demonstrated that A. muciniphila has the potential to act as a probiotic because it could exert a glucose-lowering effect by regulating gut barrier integrity through increased expression levels of tight junction proteins [33,34]. Similar to the results of these studies, we also found an increased population of A. muciniphila and strengthened gut epithelial integrity and mucus secretion capacity.…”
Section: Il-6 Il-10 Cldn1 Muc2mentioning
confidence: 99%
“…As an extremely interesting multitarget diterpenoid lactones, in recent years, andrographolide has attracted considerable number of interests in the medicinal chemistry society with its potential multiple pharmacological activities such as antiinflammatory (Ding et al, 2017), antioxidant (Mussard et al, 2019; Zhang et al, 2020), anticancer (Farooqi et al, 2020; Sato et al, 2018; Zhang et al, 2017), antimicrobial (Gupta, Mishra, & Ganju, 2017; Panraksa, Ramphan, Khongwichit, & Smith, 2017; Shi et al, 2020; Srivastava, Garg, Srivastava, & Seth, 2021), antihyperglycemic (Su et al, 2020) and regulating blood lipid (Lin et al, 2018), immunoregulation (Zhang, Yang, Du, & Guo, 2020), improving memory impairment (Das, Mishra, Ganju, & Singh, 2017), as well as mitigating cartilage damage (Chen, Luo, & Chen, 2020) and so on (Figure 2). In view of the increasing awareness of the side effects of chemotherapy drugs, this medicinal ingredient may serve as one of the backbones for the treatment of related diseases in the future.…”
Section: Introductionmentioning
confidence: 99%